Urinary hyaluronidase activity is closely related to vasopressinergic system following an oral water load in men: a potential role in blood pressure regulation and early stages of hypertension development - Calvi, Anna; Bongrani, Alice; Verzicco, Ignazio; Figus, Giuliano; Vicini, Vanni; Coghi, Pietro; Montanari, Alberto; Cabassi, Aderville (Frontiers in Endocrinology, 2024)
INTRODUCTION: Blood pressure (BP) regulation is a complex process involving several factors, among which watersodium balance holds a prominent place. Arginin-vasopressin (AVP), a key player in water metabolism, has been evoked in hypertension development since the 1980s, but, to date, the matter is still controversial. Hyaluronic acid metabolism has been reported to be involved in renal water management, and AVP appears to increase hyaluronidase activity resulting in decreased high-molecular-weight hyaluronan content in the renal interstitium, facilitating water reabsorption in collecting ducts. Hence, our aim was to evaluate urinary hyaluronidase activity in response to oral water load in hypertensive patients (HT, n=21) compared to normotensive subjects with (NT+, n=36) and without (NT-, n=29) a family history of hypertension, and to study its association with BP and AVP system activation, expressed by serum copeptin levels and urine Aquaporin 2 (AQP2)/creatinine ratio. METHODS: Eighty-six Caucasian men were studied. Water load test consisted in oral administration of 15-20 ml of water/kg body weight over 40-45 min. BP, heart rate, serum copeptin, urine hyaluronidase activity and AQP2 were monitored for 4 hours.In response to water drinking, BP raised in all groups with a peak at 20-40 min. Baseline levels of serum copeptin, urinary hyaluronidase activity and AQP2/creatinine ratio were similar among groups and all decreased after water load, reaching their nadir at 120 min and then gradually recovering to baseline values. Significantly, a blunted reduction in serum copeptin, urinary hyaluronidase activity and AQP2/creatinine ratio was observed in NT+ compared to NT-subjects. A strong positive correlation was also found between urinary hyaluronidase activity and AQP2/creatinine ratio, and, although limited to the NT-group, both parameters were positively associated with systolic BP. DISCUSSION: Our results demonstrate for the first time the existence in men of a close association between urinary hyaluronidase activity and vasopressinergic system and suggest that NT+ subjects have a reduced ability to respond to water loading possibly contributing to the blood volume expansion involved in early-stage hypertension. Considering these data, AVP could play a central role in BP regulation by affecting water metabolism through both hyaluronidase activity and AQP2 channel expression.